A primer for working with the Spatial Interaction modeling (SpInt) module in the python spatial analysis library (PySAL) - Oshan, Taylor M (REGION, 2016)
This primer provides a practical guide to get started with spatial interaction modeling using the SpInt module in the python spatial analysis library (PySAL).